The Relationship Between Posttraumatic Stress Disorder Symptoms and Posttraumatic Growth Among HIV-Infected Men Who Have Sex With Men in Beijing, China: The Mediating Roles of Coping Strategies - Ye, Zhi; Chen, Lihua; Lin, Danhua (Frontiers in Psychology, 2018)
The traumatic experience of contracting and living with HIV/AIDS may produce a myriad of mental health problems, especially posttraumatic stress disorder (PTSD) symptoms, and conversely, bring posttraumatic growth (PTG), that is, positive changes resulting from a struggle with trauma. The growing body of research into the relationship between PTSD symptoms and PTG has produced mixed results. In addition, some research has suggested that psychosocial and cognitive factors may mediate the development of PTG after trauma exposure. Specifically, individuals experience fewer psychological symptoms and better mental health when adaptive coping strategies align with stressors; however, little research is available on the relationship and the mediating effect of coping strategies on the link of PTSD symptoms and PTG among HIV-infected men who have sex with men (MSM) in China. The aims of the current study were, therefore, to investigate the relationship between PTSD symptoms and PTG as well as the potential mediating effects of coping strategies through which PTSD symptoms contributes to PTG among this vulnerable population. One hundred and forty HIV-positive MSM were recruited from the Beijing Center for Disease Prevention and Control and were asked to complete a battery of self-administered questionnaires, covering sociodemographic and HIV-related characteristics, coping strategies (i.e., problem-solving, seeking social support, self-blame, and wishful thinking), PTSD symptoms, and PTG. Results showed that, after controlling for sociodemographic and HIV-related variables, a negative linear relationship was found between PTSD symptoms and PTG. In addition, problem-solving and self-blame played significant mediating roles in the association between PTSD symptoms and PTG. The mediating effects of seeking social support and engaging in wishful thinking on the PTSD symptoms and PTD link were, however, nonsignificant. The present study contributes to an understanding of the association between PTSD symptoms and PTG and underscores the mediators through which individuals gain growth from traumatic experience in the context of HIV infection in Beijing, China. Given these findings, the future efforts at psychological intervention should differentiate and target various types of coping strategies, especially focusing on enhancing problem-solving skills and decreasing self-blame, in response to the promotion of positive growth among HIV-infected MSM.